2020
DOI: 10.1017/dmp.2020.151
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Communication in Time of Crisis: Readability of On-Line COVID-19 Information

Abstract: Objective: The purpose of this study was to assess the readability of information on the Internet posted about coronavirus disease 2019 (COVID-19) to determine how closely these materials are written to the recommended reading levels. Methods: Using the search term "coronavirus," information posted on the first 100 English language websites was identified. Using an online readability calculator, multiple readability tests were conducted to ensure a comprehensive representation would result. Results: The mean r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 10 publications
8
79
0
2
Order By: Relevance
“…Whilst there has been a surge in the number of users accessing the Government's material on public health, whether the information is intellectually accessible and understandable is another question. Basch et al investigated the readability of public health material to the average native-English speaking American and had shown that much of this literature was of an average to-high grade reading level which is out of the grasp of many [6]. With the gravity of the public health crisis, it is imperative that this information is not only physically accessible to the average layman but also intellectually available.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there has been a surge in the number of users accessing the Government's material on public health, whether the information is intellectually accessible and understandable is another question. Basch et al investigated the readability of public health material to the average native-English speaking American and had shown that much of this literature was of an average to-high grade reading level which is out of the grasp of many [6]. With the gravity of the public health crisis, it is imperative that this information is not only physically accessible to the average layman but also intellectually available.…”
Section: Introductionmentioning
confidence: 99%
“…On reviewing the published literature on PubMed using the search terms ‘readability’, ‘reading’, ‘quality’, ‘online’, ‘coronavirus’ and ‘COVID-19’, we discovered four other articles with similar methodologies, reviewing either the quality or readability of COVID-19 information online. 4 , 5 , 6 , 7 The compiled results of all the studies are represented in Table 1 . The findings of these other studies reflect the conclusions of Szmuda et al., with the average United States reading level of Websites across readability scores ranging from 8th to 11th grade.…”
mentioning
confidence: 99%
“…To date, COVID-19 caused by SARS-Co-V-2 is the fifth documented pandemic following the 1918 Spanish flu (H1N1), the 1957 Asian flu (H2N2), the 1968 Hong Kong flu (H3N2), the 2009 Pandemic flu (H1N1), with 50 million, 1.5 million, 1 million and 300,000 deaths, respectively [ 28 ]. As research points to the fact that written material on this topic is often difficult to read [ 29 ], public health education on YouTube can be an important element of a more comprehensive strategy to community mitigation efforts.…”
Section: Discussionmentioning
confidence: 99%